Sovereign Equality vs. Unilateral Enforcement: The Legality of Head-of-State Abduction and the Erosion of Immunity Ratione Personae - Drajat, Harwita Sari (The Southeast Asia Law Journal, 2026)
This research analyses the legal implications of unilateral United States intervention in Venezuela through the forced extraterritorial extraction of a legitimate head of state under the pretext of combating narcoterrorism. Utilizing normative legal research with statutory and conceptual approaches, this article deconstructs the sharp contradictions between such actions and the principles of territorial sovereignty and the doctrine of personal immunity (immunity ratione personae). The findings demonstrate that this forced extraction constitutes an internationally wrongful act that violates both customary international law and the United Nations Charter. This article further asserts that the doctrine of male captus, bene detentus has become obsolete within the modern due process of law paradigm, where narcotics charges are frequently politicized as a pretext for strategic economic interests, specifically the control of oil reserves. Additionally, this study evaluates the roles of the United Nations and the International Court of Justice, noting that their effectiveness is often hampered by the political realities of the veto power within the Security Council. In conclusion, the strengthening of international norms is imperative to prevent the disruption of global stability caused by superpower hegemony that disregards the rule of law.